THE HISTORY OF THE ORIGIN OF AMIR TEMUR - Toshpulatov Bekzod Shukhratovich; Mahmudov Bekzod Eshqobil oglu (Western European Studies, 2025)
The article provides information about Sahibqiron Amir Temur and his origin, as well as from which lineage he descended. In addition, it describes the name by which he was mentioned in many historical books.
Keywords: Taragay bahodir; Tegina begum; Sadr ash sha'riat